WORKSHOP AUTOCAD 2D DI SMK NEGERI 1 SUAK TAPEH KABUPATEN BANYUASIN - Herri Purwanto; Adiguna Adiguna; Amiwarti Amiwarti; Agus Setiobudi; Syahril Alzahri; Muhammad Firdaus (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
Community Service Activities (PPM) carried out by lecturers of the Civil Engineering Study Program, PGRI Palembang University at SMK Negeri 1 Suak Tapeh, Banyuasin Regency, aims so that students and teachers can get to know and increase knowledge about the basics of drawing a construction design using the 2D autoCAD application, basic by drawing simple shapes such as trapezoid, circle and simple house, and being able to operate and apply the AutoCAD 2D application program in teaching and learning activities in schools. The method or method applied is to provide theoretical explanations orally and practice directly in the school computer laboratory. The number of participants who attended was 30 students, most of whom did not know autoCAD. After participating in and practicing directly, of the 30 students who took part in this workshop based on the results of monitoring on the student's computer screen, it was seen that almost 90% of students could follow well and could draw according to the instructor's direction. There are 7% of students who have not been able to follow optimally with the condition that the pictures made are not in accordance with the provisions and there are 3% of students who cannot follow due to problems on the computer used